Projeto professor diretor de turma: recontextualizações de políticas na escola - Pereira, Brena Kesia Costa (Universidade Federal Rural do Semi-Árido, 2019)
This study is a discussion of the recontextualization process of the policy known as “Projeto Professor Diretor de Turma” (Teachers as Class-Directors Project - TCDP) in the educational context, from its inception through its actualization in practice. Our premise theorizes that policies of the sort are subject to recontextualization processes that arise from particular demands and processes of articulation and resistance, which in turn take place amidst power struggles; policy enactment is therefore understood as no menial task. It is our guiding assumption that the teachers participating in this research often recontextualize the above policies with a view to enabling a curriculum which facilitates teaching and learning. In order to examine this trajectory, we have elected the policy known as the ―Teachers as Class-Directors Project‖, currently undergoing implementation in secondary-education classrooms at public schools in the State of Ceará, having begun in 2008. We hypothesize that policies may be recontextualized by those actively responsible for their execution in order to decenter instruments of power, thus renouncing notions of policy implementation in educational contexts. Theoretical footing on the theory of the Continuous Policy Cycle was procured in the works of Ball (1993), Bowe; Ball (1992), Ball; Maguire and Mainardes (2006). Curriculum studies were discussed from the perspectives of Lopes (2011), Lopes; Macedo (2006), Ball (2016) and Silva (2017). Finally, in order to bring our theoretical chapter to closure, though tentatively, we cast reflections on the notion of performativity in educational contexts according to the discussions put forward by Ball (2005; 2010) and Silva (2017). This was a qualitative study whose principal collection instruments were interviews comprising a semi-structured questionnaire answered by teachers involved in TCDP‘s as Class-Directors. Official project documentation was analyzed herein as well. From their very first versions, the recontextualizations put forth by the Project have been affected by the state government‘s policy assessment practices. In the educational context itself, the school managers make attempts at policy implementation while the Class-Director Teachers, who are placed in actual charge of the Project and invariably come under pressure from management, try and recontextualize said policy when fulfilling their duties within the confines of the school context but also considering the contexts from which their students stem. These recontextualizations are made at each Class-Director Teacher‘s discretion, in line with what they deem to be adequate and according to their interests, seeing as they do not believe to have a sufficient class load at their disposal to perform their duties. . Some of the perceived recontextualizations near perspectives of personal relationships, thus translating the policy into a medium for the resolution of students‘ personal problems. These are verifiable from the moment the Class-Director Teachers tackle the execution of the policy. They feel compelled to help their students owing to the emergence of affective elements in their relationship. Such efforts are invariably justified by attempts to motivate students and help them succeed in life.
Keywords: Projeto Professor Diretor de Turma; Recontextualização; Contexto Escolar; Teachers as Class-Directors Project; Recontextualization; School Context; MULTIDISCIPLINAR::ENSINO